Personal networks and crime victimization among Swedish youth. Issue 2 (3rd July 2018) - Mollenhorst, Gerald; Edling, Christofer; Rydgren, Jens
ABSTRACT: We combine routine activity theory, lifestyle-victimization theory, and a social network perspective to examine crime victimization. In particular, we study to what extent crime victimization is associated with having close contacts who have been victimized and/or who engage in risky lifestyles. We use the data (collected in 2014) of 1, 051 native Swedes and 1, 108 Iranian and Yugoslavian first- or second-generation immigrants in Sweden who were all born in 1990. They were asked to describe their personal characteristics, various behaviours, and past personal experiences with crime victimization, as well as those of the five persons with whom they most often spend their leisure time. Our findings support the network perspective: crime victimization is negatively associated with the number of close contacts an individual mentions but is substantially more likely for those who have many close contacts who have themselves been victimized. In terms of a risky lifestyle that may enhance the likelihood of being victimized, we found only that individuals who get drunk frequently were at somewhat higher risk of being victimized. To guard young individuals against crime victimization, it might thus be worthwhile to focus more on with whom they associate than on their potentially risky lifestyles or attitudes.